2014
DOI: 10.1104/pp.114.249037
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Root Cortical Cell File Number Improves Drought Tolerance in Maize

Abstract: ORCID ID: 0000-0002-7265-9790 (J.P.L.).We tested the hypothesis that reduced root cortical cell file number (CCFN) would improve drought tolerance in maize (Zea mays) by reducing the metabolic costs of soil exploration. Maize genotypes with contrasting CCFN were grown under wellwatered and water-stressed conditions in greenhouse mesocosms and in the field in the United States and Malawi. CCFN ranged from six to 19 among maize genotypes. In mesocosms, reduced CCFN was correlated with 57% reduction of root respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
159
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(169 citation statements)
references
References 67 publications
10
159
0
Order By: Relevance
“…Chimungu et al (2014) and Jaramillo et al (2013) reported that larger cells of the root cortical parenchyma reduce cellular respiration in this region, contributing to the deepening of the root system due to a lower metabolic cost, and that corn plants with lower cortex have higher drought tolerance, due to the smaller number of cell rows. Aerenchyma in corn roots may have the function of supporting a greater soil and water acquisition, since these structures decrease the metabolic cost of growing roots because of the reduced presence of cells in respiration (Zhu et al, 2010;Souza et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chimungu et al (2014) and Jaramillo et al (2013) reported that larger cells of the root cortical parenchyma reduce cellular respiration in this region, contributing to the deepening of the root system due to a lower metabolic cost, and that corn plants with lower cortex have higher drought tolerance, due to the smaller number of cell rows. Aerenchyma in corn roots may have the function of supporting a greater soil and water acquisition, since these structures decrease the metabolic cost of growing roots because of the reduced presence of cells in respiration (Zhu et al, 2010;Souza et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…For BRS 1030, the highest length was found when stress imposition occurred at the V5, VT, and R3 stages. Chimungu et al (2014), while evaluating tolerant corn genotypes in a greenhouse, reported higher specific root length at early stages (seedlings).…”
Section: Resultsmentioning
confidence: 99%
“…Root cortical phenes are important for plant performance, particularly under edaphic stress (Zhu et al 2010;Chimungu et al 2014a;Chimungu et al 2014b;Saengwilai et al 2014;Schneider et al 2017b). Root phenes that reduce root metabolic costs including RCS, RCA, cortical cell file number, and cortical cell size reduce carbon and nutrient costs for soil exploration (Chimungu et al 2014a;Lynch et al 2014;Saengwilai et al 2014;Chimungu et al 2014b;Schneider et al 2017a).…”
Section: Rcs and Nutrient Remobilizationmentioning
confidence: 99%
“…Root phenes that reduce root metabolic costs including RCS, RCA, cortical cell file number, and cortical cell size reduce carbon and nutrient costs for soil exploration (Chimungu et al 2014a;Lynch et al 2014;Saengwilai et al 2014;Chimungu et al 2014b;Schneider et al 2017a). RCS is a promising breeding target for improved soil resource acquisition.…”
Section: Rcs and Nutrient Remobilizationmentioning
confidence: 99%
See 1 more Smart Citation